Design and optimization of gradient wettability pore structure of adaptive PEM fuel cell cathode catalyst layer. (15th April 2022) - Wan, Yue; Qiu, Diankai; Yi, Peiyun; Peng, Linfa; Lai, Xinmin
Highlights: A type of gradient wettability cathode CL with three sub-layers is designed. Gradient CL's performance (895 mW/cm 2 @0.6 V) is higher than normal (721 mW/cm 2 @0.6 V). This CL can adapt high current density, cathode humidity and air stoichiometry. Gradient CL with best performance is found through comparison of 18 structures. Abstract: The design of cathode catalyst layer (CL) is essential to improve the mass transfer capacity of proton exchange membrane (PEM) fuel cell and increase power density. In this work, cathode CL is divided into three sub-layers, and each sub-layer is added nano-particles with different wettability. The gradient CL with hydrophilic SiO2 particles at inner layer and hydrophobic polytetrafluoroethylene (PTFE) particles at outer layer significantly enhances the performance of membrane exchange assembly (MEA). Its performance is 895 mW/cm 2 @0.6 V, which is 24.1 %higher than CL without any particles (721 mW/cm 2 @ 0.6 V). Under operating conditions of high current density, high cathode humidity and high air stoichiometry, the gradient CL has only a little voltage loss. Through Electrochemical Impedance Spectroscopies (EIS) impedance analysis under high current density (1.8A/cm 2 ), mass transfer resistance of gradient CL is 25.4 Ω, and is much smaller than the mass transfer resistance of the homogeneous CL of 35.1 Ω, which reflects the significant enhancement in mass transfer capacity of gradient CL. The gradient catalyst layer is suitable for a wider range of current density, humidity, and stoichiometry, but excessive cathode gas stoichiometry causes a decrease in performance, which is caused by excessive drainage capacity. In addition, 18 different gradient CLs are designed and manufactured, and the gradient CL with catalyst coated membrane (CCM) structure has the best performance. In gradient CL, increasing the capillary pressure difference between sublayers is the key to performance improvement. It is confirmed that the property of MEA with appropriate wettability gradient design can be significantly improved.